Structural Analysis of Amylin and Amyloid β Peptide Signaling in Alzheimer’s Disease - Longsheng Xie; Christopher Lockhart; Steven R. Bowers; Dmitri K. Klimov; Mohsin Saleet Jafri (Biomolecules)
Amylin and amyloid β belong to the same protein family and activate the same receptors. Amyloid β levels are elevated in Alzheimer’s disease. Recent studies have demonstrated that amylin-based peptides can reduce the symptoms of Alzheimer’s disease in animal models. Replica exchange molecular dynamics simulation machine learning, as well as other computational analyses, were applied to improve the understanding of the amino acid residues in these amylin-based peptides. Comparisons were made between amylin, amylin-based peptides, and amyloid β. These studies converged on amylin residues 10Q, 28S, 29S, 30T, 31N, 32V, 33G, 34S, and 35N (residues 10 and 28–35) being ranked highest, meaning that they were the most likely to be involved in activating the same targets as amyloid β. Surprisingly, the amyloid β signaling domain most closely matched amylin residues 29–35 in the simulated structures. These findings suggest important residues that are structurally similar between amylin and amyloid β and are thus implicated in the activation of the amylin receptor.